Incisional Hernia after Renal Transplantation and Its Repair with Propylene Mesh - Mahdavi, Reza; Mehrabi, M (Urology Journal, 2009)
Purpose: Kidney recipients are susceptible to incisional hernia. We studied predisposing factors for incisional hernia in our patients and the results of its repair with propylene mesh. Materials and Methods: From 1989 to 2002, 589 patients had undergone kidney transplantation in our hospital. Of these, patients who developed incisional hernia were evaluated in this study. The following data were collected from their records: age, gender, weight, age at graft rejection, surgical complications, treatment method, and the treatment results with propylene mesh. Results: Of 589 recipients, 16 (3%) developed incisional hernia in surgical site. The median interval between kidney transplantation and developing of incisional hernia was 48 (range 12 to 425) days. Predisposing factors were overweight, age over fifty years, and female gender (P < 0.005). In four patients, hernia was small, and the repair was performed without using mesh. Three patients were reluctant to hernia repair, and in 9, due to the large size of hernia, repair was done using propylene mesh. Having these 9 patients treated with propylene mesh, 2 developed serous collection in surgical site, which were managed successfully with multiple punctures. Hernia recurrence or infection was not noted in these patients during 3 to 36 months follow-up periods. Conclusion: Incisional hernia is not a rare entity after kidney transplantation.Â Predisposing factors, such as overweight, age over 50 years, and female gender have a role in its development. Also, repeated surgeries in kidney recipients can increase the risk of incisional hernia. Managing this complication with propylene mesh is a safe and effective method.